The metabolic signature of cardiovascular disease and arterial calcification in patients with chronic kidney disease. (June 2022) - Sørensen, Ida MH.; Bisgaard, Line S.; Bjergfelt, Sasha S.; Ballegaard, Ellen LF.; Biering-Sørensen, Tor; Landler, Nino E.; Pedersen, Tanja X.; Kofoed, Klaus F.; Lange, Theis; Feldt-Rasmussen, Bo; Bro, Susanne; Christoffersen, Christina
Abstract: Background and aims: The relationship between chronic kidney disease (CKD) and cardiovascular events is well-established. Clinically recognised risk factors of cardiovascular disease cannot fully explain this association. The objective of the present cross-sectional study was to investigate associations between serum metabolites and prevalent cardiovascular disease, as well as subclinical cardiovascular disease measured as coronary artery calcium score (CACS) in patients with CKD. Methods: More than 200 preselected metabolites were quantified using nuclear magnetic resonance spectroscopy in 725 patients and 174 controls from the Copenhagen CKD Cohort. CACS was determined by computed tomography. Results: Mean age of patients was 57.8 years, and 444 (61.3%) were men. Most of patients had hypercholesterolemia, and 133 (18.3%) had type 2 diabetes. Overall, 85 metabolites were significantly associated with prevalent cardiovascular disease in a model adjusted for eGFR, age, and sex, as well as Bonferroni correction for multiple testing ( p  < 0.001). After further adjusting for diabetes, BMI, smoking, and cholesterol-lowering medication, the significance was lost for all but six metabolites (concentration of ApoA-1, cholesterol in total HDL and HDL2, total lipids and phospholipids in large HDL particles, and the ratio of phospholipids to total lipids in smaller VLDL particles). Of the 85 metabolites associated with prevalent cardiovascular disease, 71 were also associated with CACS in a similar pattern. Yet, in the model adjusted for all seven cardiovascular risk factors, only serum glucose levels and the ratio of triglycerides to total lipids in larger LDL particles remained significant. Conclusions: In patients with CKD, associations with prevalent cardiovascular disease were mainly found for HDL-related metabolites, while CACS was associated with glucose levels and increased triglycerides to total lipids ratio in LDL particles. Graphical abstract: Image 1 Highlights: 85 metabolites were associated with cardiovascular disease (CVD). 84 metabolites were associated with coronary artery calcium score (CACS). After risk factor adjustment CVD was associated with HDL-related metabolites. CACS was associated with glucose and triglycerides in larger LDL particles. Metabolites other than LDL cholesterol may contribute to CVD in chronic kidney disease (CKD).